2018
DOI: 10.1007/s00784-018-2626-4
|View full text |Cite
|
Sign up to set email alerts
|

Oral exfoliative cytology and corrosion of metal piercings. Tissue implications

Abstract: We propose the use of exfoliative cytology to monitor corrosion processes and for routine clinical follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…These findings support a strong role of titanium dissolution products in peri‐implantitis, which may indirectly result in a shift of the peri‐implant microbiome toward dysbiosis. In corroboration, recent studies focusing on potential causative factors of peri‐implantitis have consistently pointed to titanium particles as being associated with peri‐implant inflammation 33,35,76,77 …”
Section: Titanium Dissolution Products Are Microbiome Community Activists That Shape Microbiome Structure and Diversitymentioning
confidence: 76%
See 1 more Smart Citation
“…These findings support a strong role of titanium dissolution products in peri‐implantitis, which may indirectly result in a shift of the peri‐implant microbiome toward dysbiosis. In corroboration, recent studies focusing on potential causative factors of peri‐implantitis have consistently pointed to titanium particles as being associated with peri‐implant inflammation 33,35,76,77 …”
Section: Titanium Dissolution Products Are Microbiome Community Activists That Shape Microbiome Structure and Diversitymentioning
confidence: 76%
“…In corroboration, recent studies focusing on potential causative factors of peri-implantitis have consistently pointed to titanium particles as being associated with peri-implant inflammation. 33,35,76,77…”
Section: Titanium Dissolution Produc Ts Are Microb Iome Communit Y mentioning
confidence: 99%
“…It should be remembered that exposure to metal ions and particles, which are components of intra-oral jewelry, contributes to the development of hypersensitivity reactions and contact allergy, on the basis of which lichen planus may develop. Lichen planus, on the other hand, poses a risk of developing squamous cell carcinoma of the oral cavity [3,5]. A very rare local complication of oral piercing infection may also be Ludwig's angina, which is an inflammation of the connective tissue of the floor of the mouth and neck, and is potentially life-threatening [14,15].…”
Section: • Capnocytophaga Spp (Cs)mentioning
confidence: 99%
“…hepatitis, HIV, tetanus, tuberculosis), and as a cause of bacterial endocarditis in susceptible patients [1,3,4]. The AAPD strongly opposes the practice of intraoral and perioral tissue piercing and the use of jewelry on intraoral and perioral tissues because of the potential for pathological conditions and after-effects associated with these practices [1,5,6]. Such strong reactions and recommendations of Polish specialists, however, are missing in the national literature.…”
Section: Introductionmentioning
confidence: 99%
“…3 A recent analysis on structures of USFDAapproved drugs administered in combination with other drugs as reported by Njardarson et al revealed that the major importance of these heterocycles in combination drugs is in variety of therapeutic uses. 4 The rich literature [5][6][7][8][9][10][11][12][13][14] on the synthesis of these USFDA-approved drugs is also gaining momentum since for the clinical use of a drug, the drug molecule has be synthesized on a pilot scale using a suitable toolbox of organic chemistry. 15 A plot of the number of publications versus year of publication performed using Sci-Finder 16 for the search string 'synthesis of heterocyclic scaffolds' revealed the increasing popularity of heterocyclic scaffolds synthesized via several organic transformations (Fig.…”
Section: Introductionmentioning
confidence: 99%